Analisis Pendapatan Usaha Tani Agroforestri Di Kawasan Hulu DAS Renggung, Kabupaten Lombok Tengah - Alfian Pujian Hadi; Agus Mulyadi Ashari (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Agricultural development in dry land has a big challenge because of the variety and high risks that exist, so that agricultural development in dry land requires special handling and may be more complicated than agriculture in paddy fields. The specific objectives of the study were to determine the types of plants cultivated by dry land farmers, identify the types of risks faced by dry land farmers, determine the perceptions of farmers and informants about each identified risk, The research method used was a descriptive method. The study was conducted in East Lombok Regency, namely in Pringgabaya District. The sample determination was carried out by "quota sampling" which was 20 dry land farmers. The determination of the final respondents was carried out by "accidental sampling". Data were collected in accordance with the research objectives, and to achieve these research objectives, appropriate analysis was carried out, but generally relying on descriptive analysis so that a clear picture of the topic being studied or the objectives being achieved was obtained. The results of the study showed that: (1) There are 21 (twenty one) types of plants cultivated by dry land farmers in East Lombok Regency, consisting of food crops, secondary crops, horticulture and plantation crops. Horticultural crops (onions, tomatoes, chilies), food crops and secondary crops are cultivated during the rainy season while plantation crops are a source of income during the dry season. The main annual crop is corn (75% of sample farmers) and the plantation crop that is most in demand by farmers is cashew (50% of samples). (2) There are 4 (four) types of risks faced by dry land farmers in different forms. These risks are production risks, natural risks, market risks and management risks. The risk most often faced by farmers is natural risks. (3) Respondent farmers and informants have the perception that natural risks have the highest risk followed by market risks, production risks and management risks.